Participatory and non-participatory forest ecosystem services valuation in Sub-Saharan Africa: a systematic literature review - Fatima Salaheldin Mohamad Ali; Jan Henning Sommer; Christian Borgemeister; Lisa Biber-Freudenberger (Discover Sustainability)
Abstract Ecosystem Services Valuation (ESV) promotes sustainable land use and biodiversity conservation. However, its effectiveness in capturing local perceptions and balancing the different demands remains unclear. This study reviews the literature on forest ESV in sub-Saharan Africa from 2000 to 2023, focusing on the use of participatory and non-participatory valuation methods. The 154 papers studied revealed several key trends: (1) A trend of increasing ESV studies post-2013 with a balanced usage of participatory (51%) and non-participatory (49%) approaches; (2) Over half of them focusing on forests in Ethiopia, Kenya, Tanzania, Madagascar and Ghana indicating a considerable knowledge gap in certain regions; (3) Participatory approaches valued all three Ecosystem Services (ES) categories: regulating, provisioning and cultural in 48% of the cases, while non-participatory studies focused primarily on regulating services (51%); (4) Economic valuation was applied in 45% of them, with nearly an even split between participatory (51.4%) and non-participatory (48.6%) methods; (5) Participatory studies majorly employed socio-cultural non-economic methods, while non-participatory ones focused on biophysical non-economic valuations; (6) Drivers of change were considered in 42% of the papers, more frequently in non-participatory studies (69.2%) than the participatory ones (30.8%); (7) Participatory methods predominantly utilised statistical modelling (47%), while non-participatory ones favoured spatial analysis with remote sensing (66%); (8) Only  17% of the participatory studies included the spatial distance between the forest providing the ecosystem service and the user of this service in their analysis. Participatory approaches incorporate local perspectives but are typically limited to smaller scales, whereas non-participatory methods enable large-scale valuation but often exclude local viewpoints. Based on our findings, we recommend conducting all types of research—participatory and non-participatory—but ideally, integrated approaches in forest ES valuation to support the effective and contextually relevant conservation strategies across Africa. Graphical Abstract